Влияние ИК подсветки на рассеяние электронов проводимости в облученных протонами с энергией 25 МэВ кристаллах n-Si - Pagava, T. A.; Chkhartishvili, L. S.; Maisuradze, N. I.; Beridze, M. G.; Khocholava, D. Z. (Publishing house "Academperiodika", 2019)
The photo-Hall effect is studied in specimens of n-Si single crystals with the electron concentration N = 6 × 1013 cm−3 irradiated with 25-MeV protons at a temperature of 300 K. The irradiated specimens revealed an anomalously high value of the electron Hall mobility, which can be explained by the formation of highly conducting inclusions in the crystal bulk with ohmic junctions at their interface with the crystal matrix. At some temperatures of the isochronal annealing, the specimens demonstrated an anomalously high electron scattering, which can be reduced by the monochromatic IR illumination with a given photon energy. The illumination deionizes electrostatically interacting deep secondary defects, which are formed in the course of isochronal annealing around the highly conducting inclusions, and screen them. A- and E-centers are shown to dominate among the screening defects.